2007
DOI: 10.1124/jpet.106.117747
|View full text |Cite
|
Sign up to set email alerts
|

Open Channel Block of A-Type, Kv4.3, and Delayed Rectifier K+ Channels, Kv1.3 and Kv3.1, by Sibutramine

Abstract: The effects of sibutramine on voltage-gated K ϩ channel (K v )4.3, K v 1.3, and K v 3.1, stably expressed in Chinese hamster ovary cells, were investigated using the whole-cell patch-clamp technique. Sibutramine did not significantly decrease the peak K v 4.3 currents, but it accelerated the rate of decay of current inactivation in a concentration-dependent manner. This phenomenon was effectively characterized by integrating the total current over the duration of a depolarizing pulse to ϩ40 mV. The IC 50 value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
3
15
1
2
Order By: Relevance
“…The lack of change in deactivation kinetics of Kv4.3 channels might indicate that 'unblocking' of the channel was not necessary for channel closing and the drug could be trapped in the deactivated channels. This phenomenon is similar to the situations described for other open channel block of Kv4.3 and Kv1.5 channels (Lacerda et al, 1997;Kim et al, 2007).…”
Section: Figuresupporting
confidence: 62%
See 1 more Smart Citation
“…The lack of change in deactivation kinetics of Kv4.3 channels might indicate that 'unblocking' of the channel was not necessary for channel closing and the drug could be trapped in the deactivated channels. This phenomenon is similar to the situations described for other open channel block of Kv4.3 and Kv1.5 channels (Lacerda et al, 1997;Kim et al, 2007).…”
Section: Figuresupporting
confidence: 62%
“…Figure 1A shows the superimposed Kv4.3 channel currents that resulted from a 500 ms depolarizing pulse to +40 mV under control conditions and in the presence of rosiglitazone. Under control conditions, the Kv4.3 currents were activated to maximum and then were rapidly inactivated as reported previously (Ohya et al, 1997;Ahn et al, 2006;Kim et al, 2007). Rosiglitazone not only reduced the peak amplitude of the Kv4.3 currents but also altered the time course of the current decay.…”
Section: Statisticsmentioning
confidence: 77%
“…It was previously reported that externally applied TCAs inhibit ion channel activity by binding to an extracellular site or by diffusing through the cell membrane to gain access to a binding site on the internal surface of the membrane (Kuo, 1998;Kim et al, 2007). However, our results argue against direct I K blocking activity.…”
Section: Amoxapine Inhibited I K 443contrasting
confidence: 56%
“…Although the mechanism by which TCAs can affect ion channel activity has not been elucidated, previous reports have suggested a direct interaction between the drugs and the ion channels (Kim et al, 2007). It was reported that the drugs can block ion channel conductance by binding within the pore itself or by allosteric inhibition produced by binding outside the pore.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1A shows the superimposed Kv4.3 currents expressed in CHO cells under control conditions and in the presence of various concentrations of genistein. Under control conditions, Kv4.3 currents were activated to a peak and then were rapidly inactivated during a 500-ms pulse of ϩ40 mV at 10-s intervals, as described previously (2,22,30). In the presence of genistein, inhibition of Kv4.3 currents was substantiated by a concentration-dependent reduction in peak current amplitude.…”
Section: Methodsmentioning
confidence: 99%